UTILIZATION OF AUDIO-VISUAL MEDIA BASED ON LOCAL WISDOM AS TEACHING AND LEARNING MEDIA ON ELEMENTARY SCHOOL EDUCATION STUDENTS DURING THE COVID-19 PANDEMIC - Delora Jantung Amelia; Ima Wahyu Putri Utami; Bahrul Ulum (Widyagogik, 2021)
ABSTRACTThe pandemic that is being felt all over the world today known as the COVID-19 pandemic is a disaster that disrupts all segments of the earth without exception education. The entire center of the crowd, be it tourist attractions, market malls to schools and colleges, decided to close. With the COVID-19 virus in Indonesia, it has had a huge impact on the education system in Indonesia. In Indonesia all learning activities are directed towards online learning which has advantages and disadvantages. Learning carried out in elementary schools also uses online / distance learning through parental guidance. The purpose of this study is to analyze the use of audio visual media based on local wisdom as. The purpose of this study was to describe the use of audio-visual media based on local wisdom as a form of learning for PGSD students during the Covid19 period, learning problems using audio-visual media and how to solve problems.The results of this study resulted in the conclusion that learning using audio-visual media has several advantages, including learning using audio-visual media based on local wisdom that can facilitate learning activities, get to know local wisdom of the local area. Learning using audio-visual media based on local wisdom also has several problems, including difficult to understand without a companion. The problem of learning using audio-visual media based on local wisdom can be overcome by the existence of a manual on the use of media and the assistance that also facilitates learning activities.Keywords: Audio Visual Media, Local Wisdom